PENGGUNAAN GADGET DAN PERKEMBANGAN SOSIAL SISWA PENGGUNANYA DI SMK LABOR BINAAN FKIP UNRI PEKANBARU - Taufik Hidayat; Elni Yakub; Tri Umari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the picture of the use of gadgets andsocial development of students of gadget users. This research method uses descriptivequantitative research type with instrument type in the form of questionnaire and dataprocessing technique using percentage. The results of this study obtained an overviewof the intensity of use of gadgets among students is very active. This can be seen fromthe long duration of gadget usage, whereas the kind of gadgets students use tend touse only one type of gadget. The use of too long gadgets also has an impact thatstudents can experience, whether physical or other impacts. While the impact ofgadgets on the social development of students did not give a significant effect. This isevidenced by the high percentage level of social development even though the studentin his daily life is very active in using gadgetsKey Words: Gadgets Usage, Social Development